2008
DOI: 10.1186/ar2533
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in undifferentiated connective tissue disease

Abstract: IntroductionBoth experimental and clinical data provide evidence that vitamin D is one of those important environmental factors that can increase the prevalence of certain autoimmune diseases such as systemic lupus erythematosus, rheumatoid arthritis, insulin-dependent diabetes mellitus, and inflammatory bowel disease. The aim of the present study was to investigate the prevalence of vitamin D insufficiency in patients with undifferentiated connective tissue disease (UCTD).MethodsPlasma 25(OH)D3 levels in 161 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 45 publications
(45 reference statements)
1
73
0
5
Order By: Relevance
“…During 2.3 years follow-up, 21.7% of patients with UCTD developed into wellestablished connective tissue disease (CTD) including SLE. Patients who progressed into CTDs had lower vitamin D levels [28]. These results suggest that vitamin D deficiency in patients with UCTD may play a role in the subsequent progression into well-defined CTDs.…”
Section: Discussionmentioning
confidence: 68%
“…During 2.3 years follow-up, 21.7% of patients with UCTD developed into wellestablished connective tissue disease (CTD) including SLE. Patients who progressed into CTDs had lower vitamin D levels [28]. These results suggest that vitamin D deficiency in patients with UCTD may play a role in the subsequent progression into well-defined CTDs.…”
Section: Discussionmentioning
confidence: 68%
“…Several studies reported lower 25OHD levels in patients with SLE compared with controls and, although some results were contradictory, a correlation with disease activity scores was found 7 . Recently, Zold, et al achieved similar results investigating 25OHD concentration in UCTD; they also linked extremely low levels of 25OHD to development toward a definite CTD 8 .…”
Section: Hypovitaminosis D In Systemic Sclerosismentioning
confidence: 73%
“…An input to further investigations might result from recent research concerning rheumatoid arthritis (RA) 5 , systemic lupus erythematosus (SLE) 6,7 , and undifferentiated connective tissue disease (UCTD) 8 . A higher risk of developing RA was associated with low dietary vitamin D intake, despite subsequently published contrasting results 5 .…”
Section: Hypovitaminosis D In Systemic Sclerosismentioning
confidence: 99%
“…Both laboratory and clinical studies have provided evidence that vitamin D deficiency is an important environmental factor that can increase the prevalence of certain autoimmune diseases, such as MS [55][56][57] , Crohn disease [58] , diabetes mellitus [59,60] , systemic lupus erythematosus (SLE) [61,62] , asthma [63] , RA [64] , Sjögren's syndrome, systemic vasculitis and antiphospholipid syndrome [65] . A correlation between reduced intake of vitamin D and prevalence of the diseases can be found, which raises the possibility that serum vitamin D level is important for the pathogenesis of autoimmune diseases.…”
Section: Functionsmentioning
confidence: 99%